From deep reading to linguistic vitality - van Schalkwyk, Phil (Literator, 2025)
Research on Xitsonga compounding examines the role of nominal prefixes and headedness (Mlambo & Matfunjwa 2025), while the analysis of Northern Sotho plant names uncovers word formation strategies that link language to ethnobotanical knowledge (Tembane 2025). Research on the reading practices of first-year students reveals a gap between prescribed materials and a wider culture of reading, raising urgent pedagogical concerns (Cekiso, Boakye & Olifant 2025). v46i1. 2130 Ntshangase, X. P., 2025, ‘Renaming as representation of community onomastic interests: A case study of Alfred Duma Municipality’, Literator 46(1), a2092. https://doi.